Command or petition? A speech act analysis of the parents' utterances in John 9:21cd - H Ito (Acta Theologica)
Although speech act theory has a great potential for a better understanding of biblical texts, as demonstrated by some excellent published monographs and articles, it has been only occassionally utilised since the introduction of this theory to New Testament scholarship. In this somewhat disappointing situation, the purpose of this article is to continue to show the validity of this approach and to develop it further in the reading of biblical texts. The utterences of the blind man's parents in John9:21cd are selected as an example for this purpose.